Transformasi Buku Kia Digital Berbasis AI Untuk Meningkatkan Pemantauan Kesehatan Ibu Hamil dan Edukasi Kesehatan Pada Bidan Praktik Mandiri Kota Bengkulu - Selvianti, Dita; Herlinda, Herlinda; Nizar, Fahrul Ikram; Asyhari, Ahmad (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The government launched the KIA BOOK as a guide containing education and early detection of health problems in pregnant women, childbirth, postpartum, and children. However, in practice, the use of the KIA Book in physical form still faces several challenges, including the risk of loss, damage, limitations in understanding the information by pregnant women, and the lack of time and resources for midwives to provide comprehensive and consistent education. By developing an AI-based Digital KIA Book, the pregnancy monitoring process can be carried out more effectively, and the education provided can be tailored to the profile and needs of each pregnant woman. The aim of this research is to produce a product in the form of an AI-based digital transformation of the KIA book to improve maternal health monitoring and health education for independent midwives in Bengkulu City. This research used RD methods with agile development. The population in this study was 80 respondents consisting of 60 pregnant women who underwent pregnancy check-ups at midwives and 20 independent midwives in Bengkulu City randomly. The research instruments included a test of application usability, compliance with antenatal care (ANC) visits, recording of Fe tablet consumption, and user satisfaction. Analysis used paired t-test and Wilcoxon statistical tests. Compliance with ANC visits increased from 68.3% to 86.7% (p 0.05), recording of Fe tablet consumption increased from 55% to 81.7% (p 0.05), 73.3% of pregnant women better understood the danger signs of pregnancy after using the application, 85% of midwives felt the application made it easier to monitor pregnant women, and 90% considered the visit reminder feature very effective, Satisfaction level: the average score of pregnant women was 78.4 (acceptable) and midwives 82.1 (excellent). The AI-based Digital KIA Book is recommended to improve health monitoring of pregnant women and health education for independent midwives in Bengkulu City. Keywords: Kia Book, Digital, Pregnant Women, Independent Practice Midwives.  ABSTRAK Pemerintah mencanangkan BUKU KIA sebagai panduan yang berisi Edukasi dan deteksi dini masalah kesehatan pada iBu hamil, bersalin,nifas dan anak. Namun, dalam praktiknya, pemanfaatan Buku KIA dalam bentuk fisik masih menghadapi sejumlah tantangan, antara lain risiko kehilangan, kerusakan, keterbatasan dalam pemahaman informasi oleh ibu hamil, serta minimnya waktu dan sumber daya bidan untuk memberikan edukasi secara menyeluruh dan konsisten. Dengan mengembangkan Buku KIA Digital berbasis AI, proses pemantauan kehamilan dapat dilakukan lebih efektif, dan edukasi yang diberikan dapat disesuaikan dengan profil serta kebutuhan masing-masing ibu hamil. Tujuan dari penelitian ini menghasilkan produk berupa Transformasi Buku KIA Digital Berbasis AI untuk Meningkatkan Pemantauan Kesehatan Ibu Hamil dan Edukasi Kesehatan pada Bidan Praktik Mandiri Kota Bengkulu. Penelitian ini menggunakan metode RD dengan pengembangan Agile. Populasi pada penelitian ini berjumlah 80 Responden terdiri dari ibu hamil 60 orang yang melakukan pemeriksaan kehamilan di bidan dan Bidan Praktik mandiri 20 orang di Kota Bengkulu secara random. Instrumen penelitian meliputi uji kegunaan aplikasi, kepatuhan kunjungan antenatal care (ANC), pencatatan konsumsi tablet Fe, dan kepuasan pengguna. Analisis menggunakan uji statistik paired t-test dan Wilcoxon. Hasil Kepatuhan kunjungan ANC meningkat dari 68,3% menjadi 86,7% (p 0,05),  Pencatatan konsumsi tablet Fe naik dari 55% menjadi 81,7% (p 0,05),  73,3% ibu hamil lebih memahami tanda bahaya kehamilan setelah menggunakan aplikasi, 85% bidan merasa aplikasi mempermudah monitoring ibu hamil, dan 90% menilai fitur reminder kunjungan sangat efektif, Tingkat kepuasan: rata-rata skor ibu hamil 78,4 (acceptable) dan bidan 82,1 (excellent). Kesimpulan Buku KIA Digital Berbasis AI direkomendasikan untuk meningkatkan pemantauan kesehatan Ibu Hamil dan Edukasi Kesehatan pada Bidan Praktik Mandiri Kota Bengkulu. Kata Kunci: Buku Kia, Digital, Ibu Hamil, Bidan Praktik Mandiri.